2023
DOI: 10.2174/1573399819666221221160136
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life among Type 2 Diabetes Patients in Southern Province of Saudi Arabia using WHOQOL-BREF: A Cross-section Study

Abstract: Background: Quality of life has become a more important health outcome with advancements in medical therapies and disease management, leading to better lives for people in general, particularly those living with chronic diseases. Diabetes has a direct impact on the physical, psychological, and social aspects of personal health. This study aimed to determine health-related quality of life (HRQOL) and its predictors in patients with type 2 diabetes. Methods: A cross-sectional study was carried out on 420 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our research showed that patients with complications had a greater chance of experiencing diminished HRQoL ( Alshayban & Joseph, 2020 ; Barua et al, 2021 ; Chantzaras & Yfantopoulos, 2022 ; Gebremariam et al, 2022 ; Gebremedhin et al, 2019 ; Hamady et al, 2022 ; Kalayou Haftu et al, 2022 ; Kang et al, 2021 ; Khunkaew et al, 2019 ; Nguyen et al, 2018 ; Sari et al, 2021 ; Tran Kien et al, 2021 ; Wonde et al, 2022 ; Wong et al, 2013 ; Zare et al, 2020 ; Zyoud et al, 2015 ). Patients suffering from renal disorders ( Shamshirgaran et al, 2016 ), hypertension, chronic kidney diseases ( Wan et al, 2016 ), and macrovascular complications ( Bourdel-Marchasson et al, 2013 ) had the lowest HRQoL scores overall.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…Our research showed that patients with complications had a greater chance of experiencing diminished HRQoL ( Alshayban & Joseph, 2020 ; Barua et al, 2021 ; Chantzaras & Yfantopoulos, 2022 ; Gebremariam et al, 2022 ; Gebremedhin et al, 2019 ; Hamady et al, 2022 ; Kalayou Haftu et al, 2022 ; Kang et al, 2021 ; Khunkaew et al, 2019 ; Nguyen et al, 2018 ; Sari et al, 2021 ; Tran Kien et al, 2021 ; Wonde et al, 2022 ; Wong et al, 2013 ; Zare et al, 2020 ; Zyoud et al, 2015 ). Patients suffering from renal disorders ( Shamshirgaran et al, 2016 ), hypertension, chronic kidney diseases ( Wan et al, 2016 ), and macrovascular complications ( Bourdel-Marchasson et al, 2013 ) had the lowest HRQoL scores overall.…”
Section: Resultsmentioning
confidence: 74%
“…In 18 primary studies, gender was determined as a significant predictor of HRQoL. Females were shown to have significantly poorer HRQoL and the most statistically significant in the physical and psychological domain ( Al Hayek et al, 2014 ; Alsayed Hassan et al, 2022 ; Alshayban & Joseph, 2020 ; Barua et al, 2021 ; Bourdel-Marchasson et al, 2013 ; Chantzaras & Yfantopoulos, 2022 ; Chew et al, 2015 ; Gebremedhin et al, 2019 ; Hamady et al, 2022 ; Natarajan & Mokoboto-Zwane, 2022 ; Nguyen et al, 2018 ; Saleh et al, 2015 ; Shamshirgaran et al, 2016 ; Tran Kien et al, 2021 ; Wan et al, 2016 ; Wonde et al, 2022 ; Zare et al, 2020 ) in particular, on the dimensions of physical functioning, emotional role, energy, emotion, social functioning, and pain ( Al Hayek et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations